Burger's Medicinal Chemistry and Drug Discovery 2003
DOI: 10.1002/0471266949.bmc103
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Agents

Abstract: This chapter surveys the clinical applications of antipsychotic agents, their therapeutic indications and adverse effects, and the use of animal models. The chapter discusses structure‐activity relationships as well as pharmacokinetics, biotransformation, drug interactions, and strategies for drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 490 publications
0
8
0
Order By: Relevance
“…As the majority of neuropsychiatric disorders, including BP, are treated with a combination of antipsychotic and mood stabilizing medications, it is often difficult to determine whether gene expression level changes in postmortem brain tissues are caused organically by the disorder or whether they are a side effect of chronic drug treatments. Unfortunately, antipsychotic medications such as haloperidol and clozapine and mood stabilizers including lithium, valproate, and carbamazepine are notorious for interacting with a wide number of targets and downstream signaling pathways and may have neurodegenerative effects independent of the neuropsychiatric disorder they are being used to treat (Altar et al, 2003, 2009; Bachmann et al, 2005; Gould et al, 2004; Lewis, 2011). The implementation of animal models (principally nonhuman primates and rodents) for drug treatment studies has been helpful to ascertain specific effects of antipsychotic/mood stabilizer treatment on gene and encoded protein expression within a few systems (notably catecholaminergic, cholinergic, GABAergic, and glutamatergic) (Cheng et al, 2008; Fasulo and Hemby, 2003; Fatemi et al, 2006; Lewis et al, 2008; Melchitzky and Lewis, 2008; O'Connor et al, 2007b).…”
Section: Expression Profiling In Neuropsychiatric Disordersmentioning
confidence: 99%
“…As the majority of neuropsychiatric disorders, including BP, are treated with a combination of antipsychotic and mood stabilizing medications, it is often difficult to determine whether gene expression level changes in postmortem brain tissues are caused organically by the disorder or whether they are a side effect of chronic drug treatments. Unfortunately, antipsychotic medications such as haloperidol and clozapine and mood stabilizers including lithium, valproate, and carbamazepine are notorious for interacting with a wide number of targets and downstream signaling pathways and may have neurodegenerative effects independent of the neuropsychiatric disorder they are being used to treat (Altar et al, 2003, 2009; Bachmann et al, 2005; Gould et al, 2004; Lewis, 2011). The implementation of animal models (principally nonhuman primates and rodents) for drug treatment studies has been helpful to ascertain specific effects of antipsychotic/mood stabilizer treatment on gene and encoded protein expression within a few systems (notably catecholaminergic, cholinergic, GABAergic, and glutamatergic) (Cheng et al, 2008; Fasulo and Hemby, 2003; Fatemi et al, 2006; Lewis et al, 2008; Melchitzky and Lewis, 2008; O'Connor et al, 2007b).…”
Section: Expression Profiling In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Most antipsychotic drugs are more effective in ameliorating the positive symptoms than the negative symptoms (Altar et al , 2003a). Examples include the ‘typical’ antipsychotics haloperidol and chlorpromazine, and the ‘atypical’ antipsychotics clozapine, thioridazine, olanzapine, ziprasidone, and aripiprazole, which produce fewer adverse side effects, such as Parkinsonian-like symptoms (Altar et al , 2003a; Taylor et al , 2008).…”
Section: Therapeutic Target and Drug Discoverymentioning
confidence: 99%
“…This approach may explain why most new drugs duplicate the efficacy and side effect profiles of their predecessors, and ameliorate only a portion of disease pathology. Most CNS diseases are treated with a combination of drugs, and some of the most effective drugs such as the antipsychotic clozapine (Roth et al , 2004; Altar et al , 1986, 2003a) and the mood stabilizers lithium, valproate, and carbamazepine (Gould et al , 2004) interact with the widest number of targets, not the fewest as one might imagine. In addition, family and association studies of DNA haplotypes show that most single gene mutations explain at best only a small portion of the variation in psychiatric, cognitive, or neurodegenerative disorders, and that better genetic association scores are obtained when multiple genes are considered (Tsuang et al , 1999; Pulver, 2000; Plomin and McClearn, 1993; Hauser and Pericak-Vance, 2000; Pericak-Vance et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Classical (typical) neuroleptics such as haloperidol (1; Fig. 1) are currently used for the treatment of this disease, but their use is associated with severe mechanism-related side effects, including induction of acute extrapyramidal symptoms (EPS) [3]. Also, these compounds are ineffective against negative symptoms of schizophrenia.…”
mentioning
confidence: 99%
“…These drugs exhibit potent antagonism at multiple receptor subtypes including serotonin and dopamine receptors, suggesting the implication of the serotoninergic system in this pathology [7]. Meltzer et al [8] suggested that in the efficacy of clozapine (2) and other atypical antipsychotics such as risperidone (3) or olanzapine (4) the most-important factor is their relative affinities for the D 2 and 5-HT 2A receptors [9]. They proposed that the ratio between the pK i for 5-HT 2A and that for D 2 may be used to discriminate atypical antipsychotics (ratio > (5) and QF 0108B (6) [16], which show high affinity for the 5-HT 2A receptor subtype, with K i values of 1.6 and 2.7 nm, respectively, compound 5 being most selective for the serotonin 5-HT 2A receptor subtype, with a 5-HT 2A /5-HT 2C K i ratio as high as 150.…”
mentioning
confidence: 99%